Identification of Aquifer Potential with the Schlumberger Configuration Resistivity Geoelectrical Method and Planning of Deep Water Wells for Clean Water Needs in the Sampang Region, Madura Island, East Java - Sukir Maryanto; Fajar Rakhmanto; Muhammad Bisma Pamungkas (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
Water is an inexhaustible resource on earth and a renewable source of energy. The raw water consumed by the people of Sampang is very limited. Based on the contour of the land, raw water can be processed into drinking water or clean water through piping and a gravity system. However, people's homes are far away, so the construction of these facilities is expensive. This research is beneficial for the government or the local community. This study uses geophysical methods that can see the earth's surface, one of which is the Schlumberger configuration resistivity geoelectric method with 7 measurement points. The lithology of the rocks in the study area includes: topsoil, claystone, claystone, sandy claystone, conglomerate rock, limestone, sandy limestone, marl, sandstone, clay sandstone. After doing detailed calculations, the results of the recapitulation of the total costs at the research location are around Rp. 250,600,00.00. Up to Rp. 287,147,000.00